Crop Variety Improvement and Its Effect on Productivity: The Impact of International Agricultural Research 2003
DOI: 10.1079/9780851995496.0315
|View full text |Cite
|
Sign up to set email alerts
|

Potato genetic improvement in developing countries and CIP's role in varietal change.

Abstract: In this chapter, the contribution of the International Potato Centre (CIP) in Peru to potato cultivar development in developing countries (Asia, sub-Saharan Africa and Latin America) is discussed, covering staffing patterns, varietal release and varietal adoption. Information on expected productivity gains from potato breeding is reviewed, and the rate of return to potato breeding at CIP is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The present study has shown that the PFR potato improvement program has made some progress in developing advanced clones (those tendered for commercial release) and commercially released cultivars with marketable tuber yields above those found for established cultivars (Fig. This, to some degree, illustrates the slow adoption of newer and more productive cultivars, which is a conservatism that is reported to be characteristic of potato production systems, in general, (Tarn et al, 1992;Veilleux and De Jong, 2007;Walker et al, 2003) and is not conducive to advancing genetic progress for tuber yield in potato production. In plant variety terms, some of these cultivars are old.…”
Section: Discussion Multilocation Testing In Potato Evaluation Trialsmentioning
confidence: 56%
See 3 more Smart Citations
“…The present study has shown that the PFR potato improvement program has made some progress in developing advanced clones (those tendered for commercial release) and commercially released cultivars with marketable tuber yields above those found for established cultivars (Fig. This, to some degree, illustrates the slow adoption of newer and more productive cultivars, which is a conservatism that is reported to be characteristic of potato production systems, in general, (Tarn et al, 1992;Veilleux and De Jong, 2007;Walker et al, 2003) and is not conducive to advancing genetic progress for tuber yield in potato production. In plant variety terms, some of these cultivars are old.…”
Section: Discussion Multilocation Testing In Potato Evaluation Trialsmentioning
confidence: 56%
“…Studies to determine the extent and type of G E effects found in historic tuber yield trials will help to determine the testing strategy for genomic studies and variety selection for potato breeding programs in future. Other studies have indicated that the contribution of genetics to improve yields has been small relative to those obtained from developments in agronomic practice (Sneep and Hendriksen, 1979;Walker et al, 2003), which seems to be contrary to reports for other staple crops (e.g., Duvick, 2005;Mackay et al, 2011). Other studies have indicated that the contribution of genetics to improve yields has been small relative to those obtained from developments in agronomic practice (Sneep and Hendriksen, 1979;Walker et al, 2003), which seems to be contrary to reports for other staple crops (e.g., Duvick, 2005;Mackay et al, 2011).…”
Section: Discussion Multilocation Testing In Potato Evaluation Trialsmentioning
confidence: 97%
See 2 more Smart Citations
“…In the 1998 Initiative, nine countries from SSA, Burundi, DR Congo, Ethiopia, Kenya, Mada gascar, Rwanda, Sudan, Tanzania and Uganda, were included in the sample for potatoes (Walker et al, 2003). In 2007, information on varietal output and adoption was updated for these same countries with the exception of Sudan (Thiele et al, 2009).…”
Section: Country Coverage Methods and Data Collectionmentioning
confidence: 99%